Probing the Atomic Structures of Synthetic Monolayer and Bilayer Hexagonal Boron Nitride Using Electron Microscopy - Tay, Roland Yingjie (2017)
Monolayer hexagonal boron nitride (h-BN) is a phenomenal two-dimensional material; most of its physical properties rival those of graphene because of their structural similarities. This intriguing material has thus spurred scientists and researchers to develop novel synthetic methods to attain scalability for enabling its practical utilization. When probing the growth behaviors and structural characteristics of h-BN, the use of appropriate characterization techniques is important. In this review, we detail the use of scanning and transmission electron microscopies to investigate the atomic configurations of monolayer and bilayer h-BN grown via chemical vapor deposition. These advanced microscopy techniques have been demonstrated to provide intimate insights to the atomic structures of h-BN, which can be interpreted directly or indirectly using known growth mechanisms and existing theoretical calculations. This review provides a collective understanding of the structural characteristics and defects of synthetic h-BN films and facilitates a better perspective toward the development of new and improved synthesis techniques.